Manusia dan Kebudayaan Kaili di Sulawesi Tengah - Andi Mattulada (Antropologi Indonesia, 1991)
In this article, the author describes the ethnography of the To-Kaili, the largest ethnics group in Central Sulawesi. To-Kaili had an important historical role in the period of Dutch colonization. At least four kingdoms tried to rebel against Dutch rule namely Moutong, Banawa, Sigi, and Kulawi. The author goes on to discuss the "modal personality" of Kaili people which covers social and religious life, ethos, language, art and literature. In the last section, he tries to predict how those people will face changes in the near future.